Exploring the benefits of using stock characteristics in optimal portfolio strategies. Issue 3 (19th February 2017) - Fletcher, Jonathan
Abstract : I examine the benefits of using stock characteristics to model optimal portfolio weights in stock selection strategies using the characteristic portfolio approach of Brandt, Santa-Clara, and Valkanov. [2009. "Parametric Portfolio Policies: Exploiting Characteristics in the Cross-section of Equity Returns." Review of Financial Studies 22: 3411–3447]. I find that there are significant out-of-sample performance benefits in using characteristics in stock selection strategies even after adjusting for trading costs, when investors can invest in the largest 350 UK stocks. Imposing short selling restrictions on the characteristic portfolio strategy leads to more consistent performance. The performance benefits are concentrated in the earlier part of the sample period and have disappeared in recent years. I find that there no performance benefits in using stock characteristics when using random subsets of the largest 350 stocks.